The end of symbiosis? Australia police–media relations in the digital age. (16th November 2016) - Ellis, Justin; McGovern, Alyce
Abstract : As the police move further into areas of traditional journalistic practice, the 'unhappy marriage' between the police and the media becomes more complex. To what extent this symbiotic relationship has allowed for transparency has varied over time, subject to political, operational and technological change. While acknowledging the police premium on access to information, this relationship is further challenged by police oversight bodies, the spread of corporate mangerialism and media decentralisation. Through qualitative interviews with Australian police, crime, court and investigative journalists, we provide a fresh perspective on this relationship from the journalists' point of view. In particular we explore the impact of digital media, social media and mobile technology on this relationship integral to maintaining public confidence in the police. This research serves as the basis for further interrogation into police perceptions of the role of the media and how an increasingly mediated public sphere is influencing public confidence in the police.